Sosialisasi dan Aksi Sosial Dalam Pencegahan Penyakit Diare di Lingkungan Pondok - Titik Nuryanti; Wiwik Muhidayati; Rahmawati; Sri Luluk (LPPM Universitas HKBP Nommensen, 2025)
Diarrhea is a common illness in Islamic boarding schools, often caused by poor sanitation and low awareness of healthy and cleanliving behaviors (PHBS). According to research conducted at Darul Hijrah Islamic Boarding School, 78% of students experience diarrhea due to inadequate sanitation. A socialization and social action program was implemented through education, hygiene training, and improved sanitation facilities, resulting in a reduction of diarrhea cases from 30 to 10 cases per month (66.7%). Students’ understanding of PHBS increased, with 85% practicing proper handwashing after the intervention. These findings highlight the importance of socialization and sanitation facilities in preventing diarrhea in boarding school environments.